Factors associated with 30-day mortality in elderly inpatients with community acquired pneumonia during 2 influenza seasons - Núria Torner; Conchita Izquierdo; Núria Soldevila; Diana Toledo; Judith Chamorro; Elena Espejo; Amelia Fernández-Sierra; Angela Domínguez; the Project PI12/02079 Working Group (Taylor & Francis Group, 2017)
Community-acquired pneumonia (CAP) refers to pneumonia unrelated to hospitals or extended-care facilities. The aim of this study was to determine factors associated with 30-day mortality in patients with CAP aged ≥ 65 y admitted to 20 hospitals in 7 Spanish regions during the 2013-14 and 2014-15 influenza seasons. Logistic regression was used to identify factors associated with 30-day mortality. The adjusted model included variables selected by backward elimination with a cut off of < 0.02. A total of 1928 CAP cases were recorded; 60.7% were male, 46.67% were aged 75-84 years, and 30-day mortality was 7.6% (n = 146). Pneumococcal vaccination had a significant protective effect (OR 0.68, 95% CI, 0.48-0.96; p = 0.03) and influenza vaccination in any 3 preceding seasons slight protective effect against CAP (OR 0.72, 95% CI, 0.51-1.02;p = 0.06). Factors significantly associated with 30-day mortality were having a degree of dependence (aOR 3.67, 95% CI, 2.34-5.75; p < 0,001); age ≥ 85 y (OR 3.01, 95% CI, 1.71-5.30; p < 0.001), liver impairment (aOR 2.41, 95% CI, 1.10-5.31; p = 0.03); solid organ neoplasm (aOR 2.24, 95% CI, 1.46-3.45; p < 0.001), impaired cognitive function (aOR 1.93, 95% CI, 1.22-3.05; p = 0.005), and ICU admittance (aOR2.56, 95% CI, 1.27-5.16; p = 0.009); length of stay (aOR 1.56, 95% CI, 1.02 - 2.40; p = 0.04) and cardio-respiratory resuscitation (aOR 7.75, 95% CI, 1.20 - 49.98; p = 0.03). No association was observed for other comorbidities such as chronic pulmonary obstructive disease (COPD) or heart conditions in the adjusted model. Offering both pneumococcal and influenza vaccination to the elderly may improve 30-day mortality in patients with CAP.